(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2022)
This study seeks to identify the role that the leadership trend plays in the management of health institutions in Iraq and its impact on improving the quality of the health service provided by analyzing some opinions of affiliates working in the Iraqi health sector where a survey list was used as a main tool for collecting primary data, as it was subjected to this analysis ( 60) of the medical staff, of whom (40) are doctors and (20) are affiliated with the rank of assistant physician, and (60) members of the administrative cadre have undergone their various job ranks and administrative specializations (department manager, auditor, observer, accountant, statistician, secretary). Reliance on statistical software (spss) in data analysis. The study resulted in important results about the necessity of adopting the pioneering approach in managing health institutions and because of its importance in managing the joints and sections of these institutions and relying on administrative specializations that have the qualifications and capabilities of management and taking into account the reduction of pressure on the shoulders of doctors to hold them responsible for management in most of these institutions. Based on the above results, the study recommends that a pioneering approach be adopted in management and authorization of management in most institutions and health sectors with regard to the institutional administrative work of professionals and administrative qualifications and to reduce dependence on doctors in management, since the doctor’s profession is focused on diagnosing disease, determining appropriate treatment and medication, and emphasizing the separation of authority The administrative decision about the medical decision and setting up mechanisms that enable the institution to promote the health services provided.